Pengaruh Pengambilan Keputusan Kepala Sekolah dan Pemotivasian Guru terhadap Supervisi Pendidikan Guru di SMP Swasta Se-Kabupaten Asahan - Situmorang, Mananda; Irwanto, Irwanto (UMSU, 2024)
This research highlights the importance of implementing educational supervision in private junior high schools, which often falls short of optimal. Findings from the analysis indicate that the role of the school principal in decision-making and teacher motivation significantly influences the implementation of educational supervision. The role of the school principal has an influence of 85.10%, while teacher motivation has an influence of 91.10%. Both factors collectively have a significant impact on the implementation of educational supervision in private junior high schools. The significant variability in the implementation of educational supervision is explained by the role of the school principal and teacher motivation, while other factors such as work motivation and work discipline also make important contributions.